2003
DOI: 10.1103/physreve.67.026409
|View full text |Cite
|
Sign up to set email alerts
|

Advanced spectroscopic analysis of 0.8—1.0-MA Moxpinches and the influence of plasma electron beams onL-shell spectra of Mo ions

Abstract: This paper presents a detailed investigation of the temporal, spatial, and spectroscopic properties of L-shell radiation from 0.8 to 1.0 MA Mo x pinches. Time-resolved measurements of x-ray radiation and both time-gated and time-integrated spectra and pinhole images are presented and analyzed. High-current x pinches are found to have complex spatial and temporal structures. A collisional-radiative kinetic model has been developed and used to interpret L-shell Mo spectra. The model includes the ground state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 17 publications
1
41
0
1
Order By: Relevance
“…There have been numerous studies that have dealt with the influence of highly energetic electrons on the intensity of x-ray lines (see, e.g., [14,[18][19][20][21][22][23][24][25][26][27]). In most of these case studies, the energetic electrons were considered to be either isotropic or with a beam-like distribution, although in the latter case the effects of polarization and anisotropy of emission lines were not taken into account except for a few papers [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies that have dealt with the influence of highly energetic electrons on the intensity of x-ray lines (see, e.g., [14,[18][19][20][21][22][23][24][25][26][27]). In most of these case studies, the energetic electrons were considered to be either isotropic or with a beam-like distribution, although in the latter case the effects of polarization and anisotropy of emission lines were not taken into account except for a few papers [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…Cependant, l'essentiel du rayonnement provient de la région du croisement, légèrement décalée vers l'anode. La structure des sources estétudiée par des sténopés de 10 m (la résolution spatiale, incluant le traitement d'image, Enfin, nous avons tenté avec succès de retrouver les raies spectrales mises enévidence sur d'autres expériences Z-pinch et X-pinch [3,4,7,8]. Les premiers résultats sont présentés figure 3.…”
Section: Résultats Et Discussionunclassified
“…It was previously shown that the ratio of the Ne-like Mo lines (3A þ 3B)/(3F þ 3G) can be used as a reliable electron density N e diagnostic tool as it is not sensitive to the hot electrons and opacity in the range of the change of N e from 5 Â 10 19 to 5 Â 10 21 cm À3 [16,17]. Fig.…”
Section: Modeling Of Line Radiation From the Combined Al And Mo X-pinmentioning
confidence: 97%
“…The Mo model was developed previously to diagnose experimental X-ray L-shell Mo spectra from 1MA UNR Zebra [16,17,10,12] and later was applied to the 470 kA Cornell XP X-pinches [17,18,11,12] as well as to the 20 MA SNL-Z wire arrays [7,8,17]. The Mg and Al models were developed to describe K-shell radiation from implosions from X-pinches and wire arrays with Al 5056 wires [13].…”
Section: Modeling Of Line Radiation From the Combined Al And Mo X-pinmentioning
confidence: 99%